Tentoonstelling Landschappen : Burssens Jan, Devos Pierre, Dudant Roger, Hublau Etienne, Raveel Roger, Van Saene Maurice, Theys Yvan, Urbin Choffray Francine, De Vogelaere Alfons, De Vuyst Gaspard, Wittevrongel Roger, Wyckaert Maurice. - Geirlandt, Karel J. (Herzele : Willemsfonds, 1964)
Burssens, Jan ; Devos, Pierre ; Dudant, Roger ; Hublau, Etienne ; Raveel, Roger ; Van Saene, Maurice ; Theys, Yvan ; Urbin Choffray, Francine ; De Vogelaere, Alfons ; De Vuyst, Gaspard ; Wittevrongel, Roger ; Wyckaert, Maurice
Tentoonstelling Landschappen : Burssens Jan, Devos Pierre, Dudant Roger, Hublau Etienne, Raveel Roger, Van Saene Maurice, Theys Yvan, Urbin Choffray Francine, De Vogelaere Alfons, De Vuyst Gaspard, Wittevrongel Roger, Wyckaert Maurice, Feestpaleis, Palace, Groenlaan, Herzele, van 26 september tot 8 oktober 1964
boek